Molecular Assay on Crimean Congo Hemorrhagic Fever Virus in Ticks (Ixodidae) Collected from Kermanshah Province, Western Iran - Mohammadian, Maria (J Arthropod Borne Dis, 2016)
BACKGROUND: Crimean-Congo Hemorrhagic Fever (CCHF) is a feverous and hemorrhagic disease endemic in some parts of Iran and caused by an arbovirus related to Bunyaviridae family and Nairovirusgenus. The main virus reservoir in the nature is ticks, however small vertebrates and a wide range of domestic and wild animals are regarded as reservoir hosts. This study was conducted to determine the infection rate of CCHF virus in hard ticks of Sarpole-Zahab County, Kermanshah province, west of Iran. METHODS: From total number of 851 collected ticks from 8 villages, 131 ticks were selected randomlyand investigated for detection of CCHF virus using RT-PCR. RESULTS: The virus was found in 3.8% of the tested ticks. Hyalommaanatolicum, H. asiaticum and Rhipicephalus sanguineus species were found to have viral infection, with the highest infection rate (11.11%) in Rh. sanguineus. CONCLUSION: These findings provide epidemiological evidence for planning control strategies of the disease in the study area.